A Novel Standard for Systematic Reporting of Neuroblastoma Surgery: The International Neuroblastoma Surgical Report Form (INSRF). Issue 3 (March 2022) - Matthyssens, Lucas E.; Nuchtern, Jed G.; Van De Ven, Cees P.; Gabra, Hany O. S.; Bjornland, Kristin; Irtan, Sabine; Stenman, Jakob; Pio, Luca; Cross, Kate M.; Avanzini, Stefano; Inserra, Alessandro; Chacon, Javier Gomez; et al.
Abstract : Objective: To create the first structured surgical report form for NBL with international consensus, to permit standardized documentation of all NBL-related surgical procedures and their outcomes. Summary of Background Data: NBL, the most common extracranial solid malignant tumor in children, covers a wide spectrum of tumors with significant differences in anatomical localization, organ or vessel involvement, and tumor biology. Complete surgical resection of the primary tumor is an important part of NBL treatment, but maybe hazardous, prone to complications and its role in high-risk disease remains debated. Various surgical guidelines exist within the protocols of the different cooperative groups, although there is no standardized operative report form to document the surgical treatment of NBL. Methods: After analyzing the treatment protocols of the SIOP Europe International Neuroblastoma Study Group, Children's Oncology Group, and Gesellschaft fuer Paediatrische Onkologie und Haematologie – German Association of Pediatric Oncology and Haematology pediatric cooperative groups, important variables were defined to completely describe surgical biopsy and resection of NBL and their outcomes. All variables were discussed within the Surgical Committees of SIOP Europe International Neuroblastoma Study Group, Children's Oncology Group, and Gesellschaft fuer Paediatrische Onkologie und Haematologie – German Association of Pediatric Oncology and Haematology. Thereafter, joint meetings were organized to obtain intercontinental consensus. Results: The "International Neuroblastoma Surgical Report Form" provides a structured reporting tool for all NBL surgery, in every anatomical region, documenting all Image Defined Risk Factors and structures involved, with obligatory reporting of intraoperative and 30 day-postoperative complications. Conclusion: The International Neuroblastoma Surgical Report Form is the first universal form for the structured and uniform reporting of NBL-related surgical procedures and their outcomes, aiming to facilitate the postoperative communication, treatment planning and analysis of surgical treatment of NBL.